Feasibility and utility of intraoperative epicardial scar characterization during left ventricular assist device implantation. (21st December 2018) - Moss, Joshua D.; Oesterle, Adam; Raiman, Michael; Flatley, Erin E.; Beaser, Andrew D.; Jeevanandam, Valluvan; Klein, Liviu; Ota, Takeyoshi; Wieselthaler, Georg; Uriel, Nir; Tung, Roderick
Abstract: Introduction: Ventricular arrhythmias (VA) after left ventricular assist device (LVAD) placement are associated with increased morbidity and mortality. We sought to assess epicardial voltage characteristics at the time of LVAD implantation and investigate relationships between scar burden and postimplant VA. Methods and Results: Consecutive patients underwent open chest epicardial electroanatomic mapping immediately before LVAD implantation. Areas of low voltage and sites with local abnormal potentials were identified. Patients were followed prospectively for postimplant VA and clinical outcomes. Between 2015 and 2017, 36 patients underwent high‐density intraoperative epicardial voltage mapping; 15 had complete maps suitable for analysis. Mapping required a median of 11.8 (interquartile range [IQR], 8.5‐12.7) minutes, with a median of 2650 (IQR, 2139‐3191) points sampled per patient. Over a median follow‐up of 311 (IQR, 168‐469) postoperative days, four patients (27%) experienced sustained VA. Patients with postimplant VA were more likely to have had preimplant implantable cardioverter defibrillator shocks (100% vs 27%; P  = 0.03), ventricular tachycardia storm (75% vs 9%; P  = 0.03), and lower ejection fraction (13.5 vs 19.0%, P  = 0.05). Patients with postimplant VA also had a significantly higher burden of epicardial low bipolar voltage points: 55.4% vs 24.9% of points were less than 0.5 mV ( P  = 0.01), and 88.9% vs 63.7% of points less than 1.5 mV ( P  = 0.004). Conclusions: Intraoperative high‐density epicardial mapping during LVAD implantation is safe and efficient, facilitating characterization of a potentially arrhythmogenic substrate. An increased burden of the epicardial scar may be associated with a higher incidence of postimplant VA. The role of empiric intraoperative epicardial ablation to mitigate risk of postimplant VA requires further study.